2023
DOI: 10.21608/epsj.2023.291732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Dietary Crude Protein, Metabolizable Energy and Ideal Amino Acids Levels on Productive Performance of Broiler Chicks

Abstract: The goal of the study was to evaluate reduced dietary crude protein and energy levels, with or without supplemental amino acids, on broiler chicks' productive performance. At one day old, 270 Arbor Acres broiler chicks were divided randomly into six equal groups, containing 45 chicks /group in three replicates (15 birds/each). The chicks were allocated to the following diets, (T1) fed basal diets (BD) of 23,21 and 18 % CP and 3000,3100 and 3200 kcal/kg diet ME ( control); (T2) fed BD reduced -3% CP and -100 kc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Diaz-Vargas et al ( 2016) also reported that broiler chicken fed with diets containing okara up to 10% did not show any detrimental effects on their growth performance and FCR (1.79-1.86). In another study, there were no differences in carcass yield when broiler chickens were fed diets with various levels of okara (El-Nagmy et al, 2004;Ibrahim, 2006). Okara can replace about 60% of the soybean meal in growing duck's diet without any change in performance (Dong et al, 2005).…”
Section: Poultrymentioning
confidence: 96%
“…Diaz-Vargas et al ( 2016) also reported that broiler chicken fed with diets containing okara up to 10% did not show any detrimental effects on their growth performance and FCR (1.79-1.86). In another study, there were no differences in carcass yield when broiler chickens were fed diets with various levels of okara (El-Nagmy et al, 2004;Ibrahim, 2006). Okara can replace about 60% of the soybean meal in growing duck's diet without any change in performance (Dong et al, 2005).…”
Section: Poultrymentioning
confidence: 96%